EVALUASI PERENCANAAN DAN PENGADAAN ASET PADA BPKBMD KABUPATEN MINAHASA UTARA - Saraun, Ferina M A.; Mawikere, Lidia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Asset is one of the elements that must be managed properly in order to produce reliable information in the financial statements regions. Martinet sectoral asset management (asset) carries a significant effect on the perfection of balance sheet presentation area. The aim of this study is to see and know the planning and procurement of assets in Financial Management Board and the Regional Property North Minahasa Regency regulatory interior minister 17 in 2007 seen from the cycle of sectoral asset management are applied as well as the completeness of the source document. The method used is qualitative method with descriptive analysis techniques. The results showed that BPKBMD North Minahasa Regency is appropriate. However, BPKBMD North Minahasa Â regency should coordinate better with all SKPD as users / persons responsible Â for the preparation of the planning and procurement of assets in order to realize the principles of Good Governance.